Konsep Diri Perempuan Di Kawasan Rawan Bencana Gunung Merapi - Mario Antonius Birowo; Dhyah Ayu Retno Widyastuti; Thomas Adi Purnomo Sidhi (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2019)
The participation of communities in disaster areas is one of the important factors of disaster management. Complexity in the disasters area affects social dynamics. The most vulnerable group in a community are women, whether the physical and psychological condition.  In the context of disaster risk reduction, it is important to consider the condition of women. To understand the phenomena, this research uses Self-concept, which is discussed by George Herbert Mead in his Interaction Symbolic Theory. This research uses descriptive_qualitative method about the women in four villages on the slope of Merapi volcano, Boyolali, Central Java. These villages are located in a dangerous area during the last Merapi’s eruption. Data were collected by some techniques, such as Focus Group of Discussion, interview, document, and observation. This research found the uniqueness self-concept of women about marriage underage, the need of education, and economic sustainability.